Emerging trends in computer aided design: focus on virtual reality as a tool in architectural education (2007)
Various efforts in the industry and academia are underway to explore the possible benefits of Virtual Reality (VR) in construction. This paper provides an overview of recent amples of successful adoption of VR technology as applications in construction. The paper also provides an outline of what Virtual Reality (VR) is, and presents a work jointly carried out at the Departments of Architecture and Computer Science of the Federal University of Technology, Akure (FUTA). The aim of the joint research is to investigate the efficiency and effectiveness of” virtual reality drawing at all stages o f a project, from initial conceptual design through detailed design, planning and preparation, to construction completion. The methodology employed was the critical examination of different building project drawings developed by the use of different computer aided drawing software such as AutoCAD, and comparing them with drawings generated by virtual reality software packages such as Vizx3D modeler. The result obtained shows that VR software provides avenue for easy manipulation of the drawing details thereby increasing the management of the construction process